The Application of Islamic Business Ethics in the Behavior of Traditional Market Vendors: A Case Study at Lambaro Central Market, Aceh Besar - Malasi, Sibram (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2024)
This study investigates the application of Islamic business ethics among fruit traders at the Lambaro Central Market in Aceh Besar. Grounded in Islamic moral philosophy, the research employs a qualitative approach to examine how daily trading practices align with five core ethical principles: tauhid (divine unity), equilibrium (justice), free will, responsibility (amanah), and ihsan (benevolence). Data were collected through field observations and in-depth interviews with selected traders and customers. The findings reveal that while the principle of free will is largely upheld—evident in the freedom given to buyers to make informed choices—other principles are inconsistently applied. Notable ethical shortcomings were found in the areas of product disclosure, weighing accuracy, and prioritization of religious obligations. The study concludes that a significant gap exists between normative Islamic business ethics and actual market behavior. It underscores the need for greater ethical awareness and institutional support to promote a morally grounded marketplace in accordance with Islamic teachings.